2018
DOI: 10.1080/19476337.2018.1448456
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial potentials of Damsissa (Ambrosia maritima) leaf powder extract added to minced beef during cold storage

Abstract: 2018) Antioxidant and antimicrobial potentials of Damsissa (Ambrosiamaritima) leaf powder extract added to minced beef during cold storage, CyTA -Journal of Food, 16:1, 642-649, ABSTRACTThe antioxidant and antimicrobial effect of Damsissa leaf powder extract (DLPE) for application to cold-stored minced beef was investigated. DLPE exhibited inhibition zones of 14.0 and 12.7 mm against Escherichia coli and Staphylococcus aureus, respectively. Total polyphenol and flavonoid contents of DLPE were 188.06 mg gallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…AMA, AMC, and AMB extracts recorded the lowest IC 50 values; indicating a relevant antioxidant ability of A. maritima. This result is in agreement with those of [11,33,34] who confirmed that isolated leads from this species showed significant antioxidant activity when assessed with different methods. Interestingly, it is conceivable that modulation of the inflammatory responses represents the most important role of oxidized lipids, thus playing a major role in the development of a variety of chronic inflammatory disorders [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…AMA, AMC, and AMB extracts recorded the lowest IC 50 values; indicating a relevant antioxidant ability of A. maritima. This result is in agreement with those of [11,33,34] who confirmed that isolated leads from this species showed significant antioxidant activity when assessed with different methods. Interestingly, it is conceivable that modulation of the inflammatory responses represents the most important role of oxidized lipids, thus playing a major role in the development of a variety of chronic inflammatory disorders [6].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, AMC extract was the richest in the case of A. maritima. This finding is similar to the results of Said et al [33], who demonstrated the richness of A. maritima in terms of flavonoids. In addition to these metabolites, A. maritima includes a variety of other secondary metabolites, such as pseudoguaianolide sesquiterpene lactones, coumarins, triterpenes, sterols, and sesquiterpene lactones [12].…”
Section: Discussionsupporting
confidence: 92%
“…Meat is preserved not only by the addition of antioxidant substances but by the long-known and used-commonly-nowadays addition of salt. This is mainly used for the production of dry-cured hams [6][7][8]. Another method is the addition of organic acids and their salts [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic antioxidants and antimicrobials have been utilized to hinder oxidative reactions, inhibit microbial growth and consequently extend the shelf life of minced meat products [ 8 ]. The growing consciousness of human health and the justified fear of synthetic compounds have created a research need to explore the utility of natural antimicrobials and antioxidants in extending the shelf-life of stored meat products while maintaining their quality and safety [ 5 , 9 ]. Various natural bio-sources, e.g., plant basic proteins [ 10 , 11 ], phycocyanin [ 12 , 13 , 14 ], milk proteins [ 15 , 16 , 17 , 18 ], herbs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], chemically modified proteins [ 29 , 30 , 31 , 32 , 33 ], probiotic bacteria as well as their produced bacteriocins [ 34 , 35 ] may provide potential natural preservatives.…”
Section: Introductionmentioning
confidence: 99%